Crashworthiness evaluation of hybrid tubes made of GFRP composite and aluminum tubes filled with honeycomb structures - Mert, Sinem K.; Güler, Mehmet Ali; Altin, Murat; Acar, Erdem; Çiçek, Adem (Journal of the Brazilian Society of Mechanical Sciences and Engineering, 2023)
Metal/composite hybrid tubes are potential candidates for crashworthy products having less weight and low cost compared to conventional crash boxes. The crashworthiness of Al/GFRP tubes created by wrapping an aluminum 6082 tube in glass fiber-reinforced plastic is the subject of this investigation. To compare the crush behavior of the empty GFRP/hybrid and honeycomb-filled hybrid circular tubes, quasi-static tests were conducted. Bundles and cracks were observed during the tests of composite and hybrid tubes. Energy absorption parameters of the numerical model were compared with the results of experiments. The crushing behavior of the GFRP and hybrid specimens was simulated using a numerical approach based on the Chang–Chang damage criteria. It is found that trigger mechanisms performed in the FE analysis can effectively model the crashing behavior of GFRP/hybrid specimens. The CFE and SEA of the empty composite tube are 95% and 29% greater than the empty hybrid tube, respectively. The effect of honeycomb filling on the energy absorption capabilities of hybrid tubes is investigated. The CFE of the honeycomb-filled hybrid tube is found to be 4.5% greater than the CFE of the empty hybrid tube.